Evaluation of cryoprotective potential of Jerusalem artichoke' inulin during freeze-drying and storage of Lactobacillus paracasei HII01 - Shuichi Yamamoto (2018)
The preservation of synbiotic preparations is the most important task than the formulation, due to the stability issues. Many advanced techniques are employed to preserve and stabilize the viability of synbiotic formulas. The current study deals with the development of freeze-dried (FD) Lactobacillus paracasei HII01 with selected commercial inulins (inulin GR, inulin SC, inulin FF), inulin extracted from Jerusalem artichoke (inulin JA), skim milk, maltodextrin #2, trehalose, and sorbitol as cryoprotectants and assessment of viability during intestinal transit and storage. The trehalose, inulin F F, and inulin JA retain the survivability of L. paracasei HII01 up to 46.1-79.5%, 19.0-51.0%, and 10.3-33.1%, respectively, whereas, the sorbitol showed least survival rate (1.4-12.7%) of L. paracasei HII01 and the FD-L. paracasei HII01 without any cryoprotectants had no viable cells. The FD-powders with the high survival of L. paracasei HII01 were selected to study the viability during gastrointestinal transit (Simulated gastric fluid, and simulated intestinal fluid of human). The FD-L. paracasei HII01 with inulins protects the survivability of L. paracasei HII01 during gastrointestinal transit more than other studied protectants. The results suggested that the storage of FD-L. paracasei HII01 with inulin JA at 4°C can retain ∼59.2% of the existence of live L. paracasei HII01 cells for 60 days than other tested commercially available inulins, while the samples stored at room temperature showed the drastic reduction in the viability. Collectively, the results suggested that the inulin JA can be used in freeze drying process of L. paracasei HII01 as a cryoprotectant, which effectively diminishes the degradation of probiotic cells during gastrointestinal transit and storage.